Logika dan Berpikir Kritis : Hubungan dan Dampak Dalam Pengambilan Keputusan - Harun Puling; Efiana Manilang; Mozes Lawalata (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
Logic and critical thinking are two core aspects of the human thought process. Logic is the ability to construct arguments consistently and accurately, while critical thinking is the ability to evaluate arguments, information, and situations objectively. In the context of decision-making, both concepts play a crucial role in ensuring rational and appropriate decisions. This article discusses the relationship between logic and critical thinking and their impact on the decision-making process. The facts presented here are an in-depth review of the importance of both concepts in the context of effective decision-making. The research methods used include literature reviews from reliable sources and analysis of these concepts.